STRATEGI PENGEMBANGAN USAHA RUMAH TANGGA ABON IKAN TUNA (Thunnus sp.) “BUNDA” - Andi Suci Anita (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2020)
Small and medium industries including household businesses really need to be developed into businesses that are able to develop independently into businesses to increase community income. Household businesses built by the community must of course take into account the potential that can support business continuity. The study was conducted on household businesses Abon Ikan Tuna "Bunda" in Lumpue Village, West Bacukki District, Parepare City. The purpose of this study is to determine the potential for household business development and formulate development strategies for household businesses. From the results of observations and interviews it can be concluded that this household business has the potential to be seen from the raw material resources, human resources, equipment resources, the environment and finance. Quantitative Analysis in this study uses the Process Hierarchy Analysis Method (AHP) so that the results obtained that an alternative sequence in business development in this household business that can be applied is the addition of marketing experts, strategies to increase product diversity development, increase production volume, conduct promotions broadly, adding equipment units, opening opportunities and expanding market networks and adding transportation equipment.